Talking about Consumption: How an Indian Middle Class Dissociates from Middle-Class Life - Margit van Wessel (Cultural Dynamics 2004; 16; 93, 2004)
Members of the middle class in the Indian city of Baroda employ a common moral Discourse on consumption, one that is shaped through the operationalization of historically rooted ideals of community, family solidarity and asceticism. These ideals are set against the experience of urban middle-class life. This discourse describes consumer culture as debased materialism, while at the same time presenting it as central to Middle-class social life. This article explores the nature of the tension apparent in this contradiction, and finds that employers of this discourse accept the inescapable nature of status battles around consumption while denying it legitimacy and real significance for the constitution of their individual selves. Modern consumption is accepted, but this acceptance is morally ambivalent. People draw on collective ideological resources to describe and interpret their individual and social selves in order to individually dissociate from what they take to be an immoral society.